Assessing the tax performance of developing countries - Christian von Haldenwang; Maksym Ivanyna (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Some countries fail to ensure that their citizens and businesses make an appropriate contribution to the financing of public tasks. But not all countries with a low tax ratio automatically fall into this category. This paper presents an approach to assess the performance of developing countries' tax systems based on aggregated data and country-specific information. Instead of defining general across-the-board criteria, the approach accounts for different development levels and other influencing factors, such as non-tax revenue and governance.
Keywords: 330